Design of reinforced concrete structures IS: 456-2000 - Raju, N. Krishna (CBS Pub, 2016)
Design of reinforced concrete structures IS: 456-2000 / Raju, N. Krishna. -- Kolkata: CBS Pub., 2016 624.1834 R162 4th ed. No. of Copies : 1